O papel da administração de melatonina na resistência à insulina - Bocanegra, Isabela Motta (Universidade Federal de São Carlos, 2025)
Insulin resistance (IR) is a metabolic condition associated with chronic diseases, especially type 2 diabetes mellitus (DM2). Obesity is one of the main triggers of this condition, promoting chronic systemic inflammation and imbalances in the regulation of serum glucose and insulin levels. Scientific studies have shown a direct relationship between obesity and IR, which is often asymptomatic. According to the Brazilian Diabetes Society (SBD), approximately 50% of individuals with IR remain undiagnosed, which contributes to the progression to DM2. Conventional treatment involves the use of pharmacological agents, such as metformin, which improve insulin sensitivity, in addition to lifestyle changes, including adopting a balanced diet and regular physical activity. However, alternative therapeutic approaches have been explored as complementary strategies, with melatonin administration standing out. In this narrative review, using scientific literature from databases such as PubMed, Scielo and health agencies, the relationship between melatonin administration and the modulation of the inflammatory process of insulin resistance was explored. Initially, the pathophysiology of IR and how this condition affects health were analyzed. This was followed by the characterization of melatonin and the main findings regarding the effects resulting from exogenous use. Finally, it was concluded that the hormone demonstrated beneficial effects in reducing oxidative stress, neutralizing reactive oxygen species (ROS) and mechanisms involved in the excessive accumulation of adipose tissue, mainly in animal models. However, more consistent studies in humans are needed to investigate the efficiency of chronic melatonin administration in reversing insulin resistance.
The role of melatonin administration in insulin resistance
Keywords: Distúrbio metabólico; Sobrepeso; Hiperinsulinemia; n-acetil-5-metoxitriptamina; Inflamação; Hiperglicemia; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA ENDOCRINA